Aspergillus infection monitored by multimodal imaging in a rat model - Pluhacek, Tomas; Petrik, Milos; Luptakova, Dominika; Benada, Oldrich; Palyzova, Andrea; Lemr, Karel; Havlicek, Vladimir (Proteomics, 2016)
Although myriads of experimental approaches have been published in the field of fungal infection diagnostics, interestingly, in 21st century there is no satisfactory early noninvasive tool for Aspergillus diagnostics with good sensitivity and specificity. In this work, we for the first time described the fungal burden in rat lungs by multimodal imaging approach. The Aspergillus infection was monitored by positron emission tomography and light microscopy employing modified Grocott's methenamine silver staining and eosin counterstaining. Laser ablation inductively coupled plasma mass spectrometry imaging has revealed a dramatic iron increase in fungi-affected areas, which can be presumably attributed to microbial siderophores. Quantitative elemental data were inferred from matrix-matched standards prepared from rat lungs. The iron, silver, and gold MS images collected with variable laser foci revealed that particularly silver or gold can be used as excellent elements useful for sensitively tracking the Aspergillus infection. The limit of detection was determined for both (107) Ag and (197) Au as 0.03 μg/g (5 μm laser focus). The selective incorporation of (107) Ag and (197) Au into fungal cell bodies and low background noise from both elements were confirmed by energy dispersive X-ray scattering utilizing the submicron lateral resolving power of scanning electron microscopy. The low limits of detection and quantitation of both gold and silver make ICP-MS imaging monitoring a viable alternative to standard optical evaluation used in current clinical settings.
Keywords: Biomedicine; Humans; Mass spectrometry; Inductively coupled plasma; Lung; Microscopy, Electron, Scanning; krysa rodu Rattus; lidé; zvířata; plíce; multimodální zobrazování; Aspergillosis; mikroskopie elektronová rastrovací; Multimodal imaging; Fungal infection; Positron-Emission Tomography; Rats; Animals; Animal model; pozitronová emisní tomografie; Aspergillus; aspergilóza; Multimodal Imaging